The Association Between LPR, Obstructive Sleep Apnea, and Asthma - A Narrative Review - Będkowska-Kuśmierek, Matylda; Złotnik, Anna; Krzysztofik, Kinga; Klamka, Antoni; Kawalec, Paulina; Bronikowski, Kamil; Ryszkowski, Maksymilian; Fornal, Krystian; Będkowska-Kuśmierek, Natalia; Zaborowska, Sabina (Journal of Education, Health and Sport, 2026)
Background: Laryngopharyngeal reflux (LPR), obstructive sleep apnea (OSA), and asthma are common disorders increasingly recognized as interconnected conditions sharing inflammatory and mechanical mechanisms. Their coexistence may worsen symptoms and reduce quality of life. Aim: To review current evidence regarding the association between LPR, OSA, and asthma, including shared pathophysiological mechanisms and clinical implications. Material and Methods: A narrative review of meta-analyses, observational studies, and clinical reports examining prevalence, pathophysiology, clinical presentation, and treatment strategies related to LPR, OSA, and asthma. Results: Studies demonstrate a significant overlap among these conditions. LPR is frequently observed in patients with OSA and asthma, while OSA prevalence is increased in asthmatic individuals. Proposed mechanisms include chronic inflammation, obesity, autonomic dysfunction, upper airway instability, and nocturnal hypoxia, creating a bidirectional cycle in which each disorder may aggravate the others. Continuous positive airway pressure (CPAP) therapy may improve reflux symptoms and asthma control, whereas proton pump inhibitor treatment for LPR often provides limited benefit. Conclusions: LPR, OSA, and asthma may represent an overlapping clinical triad rather than isolated diseases. Awareness of their coexistence may improve diagnosis and support multidisciplinary management. Further prospective studies are needed to clarify causal relationships and optimize treatment strategies.